2022
DOI: 10.3389/fimmu.2022.908015
|View full text |Cite
|
Sign up to set email alerts
|

Oregano Essential Oils Mediated Intestinal Microbiota and Metabolites and Improved Growth Performance and Intestinal Barrier Function in Sheep

Abstract: With the increased demand for safe and sustainable alternatives to growth promoting antibiotics in the livestock industry, oregano essential oils (OEO) and Lactobacillus reuteri (LR) have been examined as alternatives to antibiotics for growth promotion and to improve animal health and performance. However, the mechanism underlying the OEO and LR mediation of sheep growth remains unknown. In this study, 16S rRNA gene sequencing and untargeted metabolomics were used to determine the role of the gut microbiota i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 82 publications
1
9
0
Order By: Relevance
“…In the present study, Firmicutes was the predominant phylum, succeeded by Verrucomicrobiota , Proteobacteria , and Bacteroidetes , which is consistent with the report by Jia et al (2022) that Firmicutes , Actinobacteria , Verrucomicrobia , and Bacterioidetes constituted the predominant phyla in the goat ileum. Dietary supplementation of UGAM altered the taxonomic composition of ileal microbiota, with notable reductions in the relative abundances of Verrucomicrobiota at the phylum level and Mycoplasma at the genus level in the present study.…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, Firmicutes was the predominant phylum, succeeded by Verrucomicrobiota , Proteobacteria , and Bacteroidetes , which is consistent with the report by Jia et al (2022) that Firmicutes , Actinobacteria , Verrucomicrobia , and Bacterioidetes constituted the predominant phyla in the goat ileum. Dietary supplementation of UGAM altered the taxonomic composition of ileal microbiota, with notable reductions in the relative abundances of Verrucomicrobiota at the phylum level and Mycoplasma at the genus level in the present study.…”
Section: Discussionsupporting
confidence: 93%
“…This results in enhanced weight gain in cattle, translating into greater earnings and more economic benefits. Moreover, OEO can modulate sheep’s small intestine microbiota to promote growth ( Jia et al, 2022 ). Furthermore, OEO can replace antibiotics in lamb diets, positively impacting meat quality ( Garcia-Galicia et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…A decrease in potentially pathogenic genera such Streptococcus, Escherichia, and Clostridium was measured with a concomitant decrease in the population of Bifidobacterium in the jejunum and cecum. The addition of oregano essential oil (52 mg/head/day) in the diet of small-tailed Han × Hu female lambs resulted in an increased average daily gain and a decrease in the feed/gain (F/G) ratio [73]. The authors observed that dietary supplementation with oregano EO promoted the enrichment in intestinal microbiota of Ruminococcus, Bifidobacterium, and Enterococcus, with the increase in the levels of indole-3-acetic acid and indole acetaldehyde.…”
Section: Effects Of Essential Oils On Gut Microbiotamentioning
confidence: 99%